Technical Efficiency: Evidence From Life And General Insurance Companies In Malaysia - Ng, Tuan Hock (2007)
In line with the call of the Goverment, the current study highlights the technical efficiency of general and life insurance companies in Malaysia using non-parametric analysis-DEA for period 1999-2004. Besides, the thesis also contributes to the insurance sector by establishing a relationship between firm-specific variables and technical efficiency change.